Incentive to invest in improving the quality in telecommunication industry - François Jeanjean (International Telecommunications Society (ITS), 2012)
This paper investigates the incentives to invest in improving the quality (as distinguished to investment in a new activity) in telecommunication industry using the empirical example of wireless markets. We highlight that investment incentives are positively related to the potential for technical progress. They also depend on market structure, competition intensity and penetration rate. We show that there is a target amount of investment for each national market that firms strive to achieve. We show that, from a social perspective, this target amount is the best amount that firms are encouraged to invest. Nonachievement of the target amount entails underinvestment, a fall in consumer surplus and welfare and may slow down technical progress. Employing a 30 countries dataset during 8 years, we have empirically found a change in investment behaviour according whether the target amount is achieved or not. A low margin per user may hamper the achievement of the target amount. As a result, the maximum consumer surplus as well as welfare occurs under imperfect competition and not under perfect competition.
Keywords: D21; D43; D92; L13; L51; L96; O12; 330; Competition; Investment; Investment incentives; Technical Progress; Regulation